Comparison between poly(azomethine)s and poly(p-phenylvinylene)s containing a di-R-diphenylsilane (R = methyl or phenyl) moiety. Optical, electronic and thermal properties. (5th October 2021) - Sobarzo, Patricio A.; Mariman, Andrea P.; Sánchez, Christian O.; Hauyon, René A.; Rodríguez-González, Fidel E.; Medina, Jean; Jessop, Ignacio A.; Recabarren-Gajardo, Gonzalo; Tundidor-Camba, Alain; Terraza, Claudio A.
Graphical abstract: This work reported the preparation of new silicon-containing oligo (azomethine)s and silicon-containing oligo ( p -phenylvinylene)s. The materials were structurally characterized (FT-IR, NMR and elemental analysis). TGA analysis showed a high thermal stability (501–538 °C) and the absorption and emission obtained were closely related with the nature of the di-R-diphenylsilane moiety incorporated in the backbone. All samples showed wide-band gaps. Highlights: New silicon-based oligomaterials with potential optoelectronic applications. Optical, electronic and thermal properties. Comparison between silylated -azomethine and -vinylene materials. Analysis of the effect promoted by the di-R-diphenylsilane (R = methyl/phenyl) moiety. Abstract: Two new silicon-containing poly(azomethine)s (PAzM-Me and PAzM-Ph) and two new silicon-containing poly(p-phenylvinylene)s (PPVSi-Me and PPVSi-Ph) were obtained from 4′, 4′''-(dimethylsilanediyl)bis([1, 1′-biphenyl]-4-carbaldehyde) and 4′, 4′''-(diphenyl silanediyl)bis([1, 1′-biphenyl]-4-carbaldehyde) with p -phenylendiamine for PAzMs or phenylenebis(methylene))bis(triphenylphosphonium) bromide for PPVSis. All polymers were structurally characterized by FT-IR, NMR and elemental analysis. The materials showed a high thermal stability (501–538 °C) with the TPS-core increasing this parameter. The absorption and emission of PAzMs and PPVSis were closely related with the nature of the silane-core in the backbone. All samples showed wide-band gaps where the TPS-core-based materials evidenced the lower energy transitions; PAzM-Ph (2.83 eV) and PPVSi-Ph (2.81 eV). This work lay the groundwork for new architectures of silane-based poly(azomethine)s and poly( p -phenylvinylene)s derivatives for potential optoelectronic applications.